A multidisciplinary approach for studying gender violence (2019)
This book is based on the concept that the World Health Organization (WHO) has on violence against women, in which it is recognized that there may be rape in marriage, in dating, or practiced by a stranger, likewise , unwanted sexual advances, sexual harassment, sexual slavery, forced fecundation, and forced marriage, among others, are manifestations that are included in the context of sexual violence against women (who, 2013). The first chapter indicates the degree of violence against women that has been lived in recent years in the city of Monteria, official data on complaints filed by women are presented and an analysis is made of the protection measures imposed by the State in these cases. The second chapter analyzes how justice undervalues sexual violence against women and points it out as a normal act of courtship between men and women. The third chapter exposes the influence that drug trafficking has had on the normalization of violence against women and its reification, based on the history of the cartels that have influenced the city of Cartago.